Interfacing: Alternate Presents in Interface Design (2024)
This project imagines an alternative present in interface design. That is, speculating possible technological objects by re-evaluating, questioning, and modifying the historically made decisions in the creation of interfaces. I use the button – due to its broad, ubiquitous, and intuitive nature – as an exploratory surface to materialize interactions that give a different character to human-computer interaction, aiming to activate the body in its use and bring back the pleasure of the analog to the digital era. Through the creation of objects that provide unstructured interactions inspired by values true to the original spirit of computing (hacking, iteration, curiosity), I propose a framework that encourages the user to explore and connect with others, ultimately helping us to rethink our interaction with machines from new perspectives.